(untitled) (Boca Raton, 2009)
Each well-developed chapter provides the fundamentals of transport phenomena and thermodynamics as they relate to the process described, a state-of-the-art literature review, and replicable case studies of extraction processes. This authoritative reference examines a variety of established and groundbreaking extraction processes including: Steam distillation; Low-pressure solvent extraction; Liquid-liquid extraction; Supercritical and pressurized fluid extraction; Adsorption and desorption
Keywords: Công nghệ thực phẩm,Extraction (Chemistry),Food industry and trade